1996
DOI: 10.1111/j.1476-5381.1996.tb16008.x
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the renin‐angiotensin system to short‐term blood pressure variability during blockade of nitric oxide synthesis in the rat

Abstract: 1 The aim of this study was to investigate, by use of spectral analysis, (1) the blood pressure (BP) variability changes in the conscious rat during blockade of nitric oxide (NO) synthesis by the L-arginine analogue N0-nitro-L-arginine methyl ester (L-NAME); (2) the involvement of the renin-angiotensin system in these modifications, by use of the angiotensin II AT,-receptor antagonist losartan.2 Blockade of NO synthesis was achieved by infusion for 1 h of a low-dose (10 jug kg-' min-', i.v., n= 10) and high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
28
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 43 publications
3
28
0
Order By: Relevance
“…Administration of PE may be analogous to baroreflex denervation in that baroreflex-mediated changes in peripheral vascular resistance may be largely attenuated because of the chronic stimulation of ␣ 1 -adrenergic receptors. Other factors have also been reported to modulate VLF BP oscillations, including the RAAS and nitric oxide (15,22). To this extent, our data are also in agreement with these previous studies, as evidenced by the ANG II-induced increase in VLF BP power, although to a significantly lesser extent compared with PE-infused rats.…”
Section: Discussionsupporting
confidence: 82%
“…Administration of PE may be analogous to baroreflex denervation in that baroreflex-mediated changes in peripheral vascular resistance may be largely attenuated because of the chronic stimulation of ␣ 1 -adrenergic receptors. Other factors have also been reported to modulate VLF BP oscillations, including the RAAS and nitric oxide (15,22). To this extent, our data are also in agreement with these previous studies, as evidenced by the ANG II-induced increase in VLF BP power, although to a significantly lesser extent compared with PE-infused rats.…”
Section: Discussionsupporting
confidence: 82%
“…Consistent with our previous report (7), BPV was lower in mice lacking ANG AT1a receptors. Pharmacological intervention with angiotensin receptor blockers also decreased BPV (22,25). Treatment with STZ produced a prominent reduction in BPV in controls with no effect in AT1aKO.…”
Section: Discussionmentioning
confidence: 92%
“…However, very low-frequency (VLF) blood pressure fluctuations (0.02-0.2 Hz in rats) at frequencies below the frequency of Mayer waves are less well understood. A variety of factors, including catecholamines (45), the renin-angiotensin system (7,18,43,44), heat stress (51), and hypovolemia (42), have been associated with VLF blood pressure variability. In addition, studies on dynamic autoregulation of local blood flow in rats demonstrated that myogenic vascular function is most effective at frequencies Ͻ0.2 Hz in the renal circulation (1, 9, 30, 53), Ͻ0.13 Hz in the mesenteric vascular bed (1), and Ͻ0.1 Hz in the cerebral circulation (27).…”
mentioning
confidence: 99%